Unpacking the complexities of MaaS business models – A relational approach. Issue 1 (31st December 2022) - Hoveskog, Maya; Bergquist, Magnus; Esmaeilzadeh, Alireza; Blanco, Harvey
ABSTRACT: Mobility as a Service (MaaS) integrates different transportation services into a single on-demand mobility service to promote sustainable mobility. A challenge is how to innovate new business models for MaaS as it demands an understanding of how various actors position themselves within a MaaS ecosystem and how value creation changes in such ecosystems. While different streams of research on MaaS business model innovation have applied an ecosystem approach, the approach has been limited to a focal actor or the relationships between a few actors. This paper reviews academic literature and consultancy reports on business models for MaaS and presents an integrated framework that describes actors' roles and relationships in MaaS ecosystems as well as types of business models. In doing so, the paper contributes to an understanding of the interlinked character of value creation and value capture – two central parts of any business model – in MaaS. Based on the findings, the paper argues that taking an ecosystem approach to the analysis of MaaS business models can be a way to fully capture the complexity of value creation and value capture in MaaS business models.